Sex Assessment from the Volume of the First Metatarsal Bone: A Comparison of Linear and Volume Measurements. Issue 6 (23rd February 2017) - Gibelli, Daniele; Poppa, Pasquale; Cummaudo, Marco; Mattia, Mirko; Cappella, Annalisa; Mazzarelli, Debora; Zago, Matteo; Sforza, Chiarella; Cattaneo, Cristina
Abstract: Sexual dimorphism is a crucial characteristic of skeleton. In the last years, volumetric and surface 3D acquisition systems have enabled anthropologists to assess surfaces and volumes, whose potential still needs to be verified. This article aimed at assessing volume and linear parameters of the first metatarsal bone through 3D acquisition by laser scanning. Sixty‐eight skeletons underwent 3D scan through laser scanner: Seven linear measurements and volume from each bone were assessed. A cutoff value of 13, 370 mm 3 was found, with an accuracy of 80.8%. Linear measurements outperformed volume: metatarsal length and mediolateral width of base showed higher cross‐validated accuracies (respectively, 82.1% and 79.1%, raising at 83.6% when both of them were included). Further studies are needed to verify the real advantage for sex assessment provided by volume measurements.